Facebook Democracy The architecture of Disclosure and the Threat to Public Life - Marichal, José (Taylor & Francis, 2012)
Drawing on a number of disciplines and an ethnographic analysis of 250 Facebook political groups, Marichal explores how Facebook's emphasis on social connection impacts key dimensions of political participation: e.g. mobilization, deliberation, and attitude formation.